Doctoral Theses Focused on Didactics of Biology in the Czech Republic between Years 2004–2013 - Pavlasová, Lenka (Scientia in educatione, 2015)
Doctoral theses are an important indicator of the quality of doctoral studies. In this study, qualitative research of 19 dissertations focused on the didactics of biology defended between years 2004–2013 was conducted by the content analysis method. The following indicators were followed: biological topics, educational level under examination, methods of data collection used in research, number of auto-citations and their quality, practical output and its characteristics. There were 64 % female authors of dissertations and 36 % men authors. Biological topics were unequally represented, some of them were completely neglected (e.g., biology of fungi). All educational levels were examined in the analysed dissertations: pre-primary, primary, lower and upper secondary and university levels (0–3, 5–6 according to ISCED97). The most frequently used method of data collection in doctoral students’ research was a questionnaire, followed by the content analysis, observations, an achievement test and an interview. The number of auto-citations in dissertations was varied. Dissertations with a small number of auto-citations usually contained some kind of a practical output and thus, they were not entirely only research ones.